Synthesis, Characterization, and Antimicrobial Activity of New Schiff’s and Mannich Bases of Isatin and Isatin Derivatives - May Mohammed Jawad Al-Mudhafar (Journal of Global Pharma Technology, 2016)
Objective: Schiff’s and Mannich bases of isatins are an important group of heterocyclic compounds which are of great importance in medicinal chemistry as antimicrobial agents. In the vision of these facts, new bis-Schiff bases and Mannich bases of isatins were synthesized. Methods: Three different bis-Schiff bases (3a-c) have been synthesized by reacting isatin, 5-fluoroisatin and 5-methoxy isatin with thiophene-2-carboxaldehyde using hydrazine hydrate to link between the carbonyl compounds, and then these bis- Schiff bases were condensed with two different secondary amines (piperidine and morpholine) separately, and formaldehyde to form the Mannich bases (4a-c and 5a-f), respectively. Results: The structures of the newly synthesized compounds were confirmed using (Fourier- transform infrared) FTIR, 1H-nuclear magnetic resonance spectroscopy (¹H-NMR) and CHNS elementary analysis. All the synthesized bis-Schiff bases and Mannich bases were screened for their antimicrobial activities. Conclusion: The target compounds showed convincing antibacterial activity, whereas their antifungal activity was more potent, and the most active ones were Mannich bases of 5-methoxy isatin derivatives (4c and 5c) against Candida albicans.Keywords: Antimicrobial activity, Bis-Schiff bases, Isatin derivatives, Mannich bases, Thiophene-2-carboxaldehyde.